2012
DOI: 10.1016/j.jvs.2012.03.263
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome and morphologic analysis after endovascular aneurysm repair using the Excluder endograft

Abstract: EVAR using the Excluder endoprosthesis provides a safe and lasting treatment for AAA, despite the need for maintained surveillance and secondary interventions. At up to 11 years, the risk of AAA-related death or postimplantation rupture is remarkably low. The incidences of postimplantation sac growth and secondary intervention were greatly reduced after the introduction of the low-permeability design in 2004.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 37 publications
1
26
1
Order By: Relevance
“…On one hand, device-specific studies of other currently commercially available stent grafts are scarce but show comparable primary clinical success rate after 3 years. 19,20 On the other hand, Pratesi et al 21 and Baptiste et al 22 reported a freedom of reintervention rate of 94.6% and 92% after 3 years. However, only approximately one-third of patients were available for analysis at this point.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, device-specific studies of other currently commercially available stent grafts are scarce but show comparable primary clinical success rate after 3 years. 19,20 On the other hand, Pratesi et al 21 and Baptiste et al 22 reported a freedom of reintervention rate of 94.6% and 92% after 3 years. However, only approximately one-third of patients were available for analysis at this point.…”
Section: Discussionmentioning
confidence: 99%
“…This occlusion rate of 4% is comparable with other studies with this particular stent graft 3,4,23 but is still substantial and seems higher compared with other simultaneously available grafts. [20][21][22] However, comparing the results is difficult because of the heterogeneity in patient population and follow-up duration.…”
Section: Discussionmentioning
confidence: 99%
“…The associations between proximal neck complications and mural neck thrombus and neck calcification are less clear in the literature, which may be caused by the diversity in onset of the complications throughout these studies. 1,2,7,9,14 When comparing our previous study 10 with this one, the results suggest that neck calcification is associated with early complications, while mural neck thrombus is rather associated with late (>1 year) sequelae. Acute complications may be associated with factors that increase the procedure difficulty (tortuous aorta) or immediately impede sufficient fixation and sealing (neck calcification); later failure may be associated with factors that do not provide a stable environment and are prone to change over time (high curvature, mural neck thrombus, and large aneurysm diameter).…”
Section: Discussionmentioning
confidence: 56%
“…3,7) Notably, Gore Excluder endoprosthesis (W.L. Gore & Associates, Flagstaff, Arizona), one of the currently available third-generation endografts, has been reported to more suitable for complex iliac anatomy, with a limb occlusion incidence of 0%-1.4%, 4,9) which is lower than that of Zenith stent graft (4.8%-5.5%) 4,6,8) or Endurant endograft (Medtronic Inc, Minneapolis, Minnesota) (3.4%). 7) Treatment modalities for endograft limb occlusion are determined by the area and length of thrombosis, pattern of disease progression, clinical presentation, and severity of leg ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Endograft occlusion, a serious late complication following EVAR, has been reported to have an incidence ranging from 1.1% to 7.1%. [1][2][3][4][5][6][7][8][9] Typically, endograft limb occlusion occurs unilaterally. If endograft occlusion occurs acutely in the bilateral limb or the main body of the endograft, its pathological condition may be similar to that of acute occlusion of the abdominal aorta, a emergency treatment.…”
Section: Introductionmentioning
confidence: 99%